Aesthetic and Ethical (Trans) Figurations in the Artistic Practices of Ayi Kwei Armah - Ndi, Gilbert Shang (Decolonial Aesthetics II : Modes of Relating, 2023)
In Ayi Kwei Armah’s texts, the figure serves as a nexus of aesthetic and ethical visions that opens the literary text to innovative and non-conventional readings, enhancing the relationship between the literary work as a mise en scene and mise en abyme of graphic signs with other art forms such as plastic arts, painting, sculpture, photography, etc. In this chapter, I set out to critically probe the nature of that figure, as represented in some of the key works of Ayi Kwei Armah. I explore the various ways in which this author employs aesthetic forms that constitute different ways of grappling with the ‘figure’ of his quest. This quest encompasses his ideological views of Africa’s past, culture and possible renaissance and the continuous re-imagination of his role as an African author in a global system in which Africa continues to occupy a marginal position. The figures of this quest take different forms in his works as he progressively perfects his creative medium and vision, depicting different facets of postcolonial realities and emergent existential challenges to the African self